العلاقة بین استخدام مواقع التواصل الاجتماعي وإدارة الوقت لدى طلبة الدراسات العلیا - الفیسبوك نموذجا – دراسة میدانیة بجامعة محمد الشریف مساعدیة سوق أھراس - بوشارب إيمان (My University, 2019)
Abstract The major role of modern technologies, especially in the scientific field, is not limited to a specific group. Rather, it has challenged us to include all segments of society due to the emergence of numerous tools, most notably social networking sites, especially Facebook, which has made numerous contributions to the scientific field. Its ease of use has enabled science students to rely heavily on it to complete their research in the shortest possible time. This has required students to consider the importance and amount of time and how to utilize it. This can only be achieved through time management on social networking sites. Hence, a problem was raised regarding the relationship between social networking sites (Facebook) and time management. We relied on the uses and gratifications approach, which controlled the study variables. Hence, our study emerged in the form of a systematic structure based on interconnected and sequential chapters to address the study's basic variables, which are social networking sites (Facebook), time management, and the relationship of this site (Facebook) to time management at Mohamed Cherif Messaadia University in Souk Ahras, the field of research. The research included four chapters that complemented each other. As for the stage of reconstructing the elements of the studied phenomenon, according to the hidden patterns revealed by the field data, we relied on a set of procedural tools for field processing, which were: analysis, interpretation, and understanding. ------------------------- الملخص: لا یقتصر الدور الرئیسي لتكنولوجیات الحدیثة وخاصة في مجال العلمي على فئة معینة بل تحداه لیشمل جمیع أطیاف المجتمع وذلك بفعل إفرازها لوسائل عدیدة ، أبرزها مواقع التواصل الاجتماعي وخاصة الفیسبوك الذي له العدید من الإسهامات في المجال العلمي فسهولة استخدامه مكنت طلاب العلم من الاعتماد علیه بصورة كبیرة في انجاز بحوثهم بأسرع مدة ، هذا ما استوجب على الطلاب مراعاة أهمیة وحجم الوقت وكیفیة استغلالهم ولا یتم ذلك الا بادارة الوقت في مواقع التواصل الاجتماعي ومن هنا تمت اثارة اشكالیة حول علاقة مواقع التواصل الاجتماعي (الفیسبوك) بادراة الوقت اعتمدنا على مقاربة الاستخدامات و الاشباعات التي ضبطت لنا متغیرات الدراسة . ومنه جاءت دراستنا في شكل بناء منهجي على أساس فصول مترابطة ومتسلسلة لمعالجة المتغیرات الأساسیة للدراسة والتي تتمثل في مواقع التواصل الاجتماعي (الفیسبوك) وإدارة الوقت وعلاقة هذا الموقع (فیسبوك ) بإدارة الوقت في جامعة محمد الشریف مساعدیة بولایة سوق أهراس ، میدان البحث ، فقد شهد البحث أربعة فصول جاءت مكملة لبعضها البعض أما في مرحلة إعادة تركیب عناصر الظاهرة المدروسة وفق الأنساق الخفیة التي كشفت عنها معطیات المیدان ، فقد اعتمدنا على مجموعة من الأدوات الإجرائیة للمعالجة المیدانیة تمثلت في : التحلیل ، والتفسیر ، والفهم
Keywords: مواقع التواصل الاجتماعي، إدارة الوقت، طلبة الدراسات العلیا، الفیسبوك م